Gouging abrasion test for rock abrasiveness testing - Golovanevskiy, Vladimir; Bearman, R. (Elsevier, 2008)
Wear parts of many mineral processing and mining equipment are often subjected to high stress loads applied at high speeds and at varying angles of incidence, where the prevalent mode of wear is high-stress gouging/sliding impact abrasion. Examples include crusher liners, wear liners in hoppers and chutes, picks on roadheaders, discs on tunnel boring machines and ground engaging tools. Abrasion under these conditions is characterised by a high material removal rate and thus has a direct bearing on wear rates and service life of the equipment concerned. However, at present there appears to be no method for rock abrasiveness assessment under these conditions. This paper describes a new Gouging Abrasion method and apparatus for testing abrasivity of rocks under high-stress gouging/sliding impact wear. A Gouging Abrasion Index (Gi) is introduced, which can be used for prediction and assessment of component life expectancy and efficiency of mineral processing and materials handling equipment. Experimental data from Gouging Abrasion testing of numerous Australian rock types are presented. It is suggested that the results of Gi testing can be used for wear rate predictions for a variety of mineral processing and materials handling equipment working under high-stress gouging/sliding impact abrasion conditions